Kajian Risiko Pengoprasian Gudang Materiil - Yani Nurita Purnawati; Nurpajriani Nurpajriani; Dahlan Dahlan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
A good warehouse management could help the organizations to minimize the costs. The operational of the warehouse is always faced with various risks. This study aims at assessing the risk of operating a material warehouse using the cause and effect diagram method. The data was collected from a survey of 30 material warehouse employees. Risk mapping is applied to the risks of human resources, machinery, methods and materials by measuring the frequency of risk and the weight of impact on organizational performance.